Embedding planetary health concepts in a pre-medical physiology subject - Moro, Christian; McLean, Michelle; Phelps, Charlotte (Medical teacher, 2023)
There are increasing calls for planetary health (which includes sustainable healthcare) to be included in tertiary health professions education. With already busy curricula, particularly in medicine, educators need to find innovative ways of integrating these important concepts without adding to learners' workload. This study investigated whether planetary health concepts could be integrated into a Physiology subject as a stop-gap approach while longitudinal planning for longitudinal curriculum integration was underway. Each week, a planetary health fact (Did you know?) with a corresponding link were embedded at the bottom of a relevant PowerPoint lecture slide to match the topic of the week in a health science and medicine Physiology subject. The embedded facts were a mix of effects on health and the environmental impacts of healthcare activities, such as medical imaging. No other formal planetary health teaching was conducted in the subject. At the end of the semester, 44% of 100 students completed a survey regarding their perceptions of the planetary health inclusions. Participants reported an appreciation of the facts, found them helpful for their overall learning, and were interested in learning about healthcare's large environmental footprint. Seventy-one percent were able to provide a reasonable definition of planetary health. Half of the participants reported their actions, behaviours, and thoughts had changed as a result of the planetary health inclusions. This study provides a relatively simple approach for individual educators to include planetary health concepts into existing health professions subjects until more longitudinal curriculum revisions can be undertaken. Based on our findings, we would, however, recommend providing students with a brief introduction in terms of why planetary health has been included either at the start of the first lecture or as a 10-min video.